Photobiomodulation in the treatment of pressure injuries: an integrative review (Research, Society and Development, 2022)
Pressure injuries can be defined as damage to the skin and adjacent soft tissues, usually over bony eminence, caused by prolonged exposure to friction, pressure and shear forces. Thus, the involvement of this type of injury in patients is directly added to the recovery and quality of life of patients. Since, due to the presence of multiple epidemiological factors, the healing of such chronic skin lesions does not occur properly. . Thus, the present study aimed, through an integrative review, to describe the benefits of photobiomodulation in the treatment of pressure injuries. In this sense, the researchers point out that low-level laser therapy works by reducing the migration of inflammatory cells (neutrophils and leukocytes). Improving edema and increasing growth factors, developing a tissue recovery process. However, the controversies regarding the standardization of the parameters to be applied in the therapy make it difficult to choose the dosage to be used. Thus, the need and importance of continuation of research covering the theme is highlighted.